2018
DOI: 10.1111/jir.12461
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of anti‐epileptic medication prescribing in the treatment of epilepsy in older adults with intellectual disabilities

Abstract: Prevalence of epilepsy was high among older people with ID, and half were exposed to two or more AEDs. Despite the use of AED therapy, over half had seizures in the previous 2 years. As the primary goals of optimal AED treatment are to achieve seizure freedom without unacceptable adverse effects, this was not achievable for many older patients with ID and epilepsy. Our findings indicated that people with ID and epilepsy were often exposed to psychotropic medications that may lower the seizure threshold. Regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
1
14
0
2
Order By: Relevance
“…It should be noted that adverse cardiovascular effects from antipsychotic drugs are common, highlighting the current findings of low prevalence of drug use for the cardiovascular system in the higher age categories in the ID sample . Also, the prevalence of anxiolytic drug use was higher in the ID sample when compared with the reference sample and is in accordance with the findings in Doan et al The prevalence of antiepileptic drug use in the ID sample was also in line with previous findings and the reported prevalence of epilepsy in people with IDs . Thus, it can be suggested that epilepsy is adequately identified and treated at an age‐independent group level.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It should be noted that adverse cardiovascular effects from antipsychotic drugs are common, highlighting the current findings of low prevalence of drug use for the cardiovascular system in the higher age categories in the ID sample . Also, the prevalence of anxiolytic drug use was higher in the ID sample when compared with the reference sample and is in accordance with the findings in Doan et al The prevalence of antiepileptic drug use in the ID sample was also in line with previous findings and the reported prevalence of epilepsy in people with IDs . Thus, it can be suggested that epilepsy is adequately identified and treated at an age‐independent group level.…”
Section: Discussionsupporting
confidence: 89%
“…27 Also, the prevalence of anxiolytic drug use was higher in the ID sample when compared with the reference sample and is in accordance with the findings in Doan et al 11 The prevalence of antiepileptic drug use in the ID sample was also in line with previous findings and the reported prevalence of epilepsy in people with IDs. 28,29 Thus, it can be suggested that epilepsy is adequately identified and treated at an age-independent group level.…”
Section: Figurementioning
confidence: 99%
“…This is (or was) the case in the UK according to a 2003 survey [115]. In a more recent Irish survey of 736 older adults with intellectual disabilities, the most prescribed drugs were valproic acid (48.7%) and CBZ (46.3%), followed by lamotrigine (27.8%) [116]. Recommendations in terms of careful CBZ dosing and serum monitoring is thus especially valuable in this population [115].…”
Section: Elderly Patientsmentioning
confidence: 99%
“…Pada sebuah studi yang dilakukan pada pasien disabilitas intelektual dewasa dengan epilepsi, penggunaan antiepilepsi yang paling sering dilaporkan adalah asam valproat (48,7%), karbamazepin (46,3%) dan lamotrigin (27,8%). 31 Pada tahun 2017, terdapat penggunaan donepezil yang langsung masuk ke dalam segmen DU 90% (dapat dilihat pada Tabel 3). Donepezil (N06DA02) merupakan obat antidemensia dan antikolinesterase.…”
Section: Pembahasanunclassified